From Meurtres pour mémoire to Missak: Literature and historiography in dialogue. (August 2014) - Atack, Margaret
Didier Daeninckx has devoted many novels to the history and memory of the Occupation. This article explores the relationship between his fiction and historiographical frameworks with reference to Meurtres pour mémoire, contrasted with Missak published 25 years later. After discussion of 1980s historiography of the Occupation and the Algerian War, it looks particularly at narrative structure and the thematics of order (both obedience and orderly documentation), seeking to establish the differences in the ways these two novels historicise the past, and the historiographical differences in their approach to guilt, knowledge and interpretation.